Ideal Cardiovascular Health in a Nationally Representative Population-Based Sample of Adults in Malawi - Pengpid, Supa (Glob Heart, 2021)
BACKGROUND: Ideal cardiovascular health (ICH) measures four ideal health behaviours (non-smoking, body mass index <25 kg/m(2), healthy diet, and physical activity) and three health factors (total cholesterol <200 mg/dL, blood pressure <120/<80 mmHg, and fasting blood glucose <100 mg/dL). OBJECTIVE: This study aimed to determine the prevalence, distribution, and correlates of ICH among adults in Malawi. METHODS: National cross-sectional survey data of 3,441 persons aged 18–69 years with complete ICH measurements in Malawi in 2017 were analysed. RESULTS: Almost one in ten (7.4%) of respondents had 0–2 ICH metric), 21.2% 3–4 ICH metrics, and 71.5% 5–7 ICH metrics). Only 3.3% had all seven ICH metrics, 15.3% had intermediate ICH (≥1 metric in the intermediate category and none in the poor category), and 81.5% poor ICH (≥1 metric in poor category). In adjusted logistic regression analysis, older age (50–69 years) (Adjusted Odds Ratio-AOR: 0.25, 95% Confidence Interval-CI: 0.17–0.36) and urban residence (AOR: 0.56, 95% CI: 0.40–0.78) were negatively associated with meeting 5–7 ICH metrics. In addition, in unadjusted analysis, higher education was positively associated with meeting 5–7 ICH metrics. CONCLUSION: The proportion of meeting 5–7 ICH metrics was high in Malawian adults. Both high-risk and population-wide intervention programmes targeting older adults and urban residents should be implemented in aiding to improve cardiovascular health in Malawi. HIGHLIGHTS: The proportion of meeting 5–7 ideal cardiovascular health (ICH) metrics was 71.5% in Malawian adults (18–69 years, median age 32 years). In a sub-group analysis (45–69 years, median age 55 years), 55.9% had 5–7 ideal ICH metrics. ICH was lower with increasing age and among urban residents.